2019
DOI: 10.3390/healthcare7010006
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Association between Physical Activity and Sleep in Community-Dwelling Persons with Dementia: An Exploratory Study Using Self-Reported Measures?

Abstract: Sleep disturbances are common in persons with dementia (PWD). While pharmacotherapy is widely used, non-pharmacological interventions are beginning to surface as first-line management strategies. This study sought to investigate if physical activity was associated with more favourable sleep patterns in PWD, and to compare the sleep quantity and quality between active and inactive PWD. We conducted an exploratory study to tackle these research questions. Self-reported telephone questionnaires were administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
(46 reference statements)
1
8
0
Order By: Relevance
“…Physical activity (PA) represents an important segment of physical and mental health status [1][2][3]. Irrespective of the importance of PA in all periods of life, reaching the appropriate PA level (PAL) is particularly important in childhood and adolescence, since regular PA is essential for healthy growth and development during this life period for a number of reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity (PA) represents an important segment of physical and mental health status [1][2][3]. Irrespective of the importance of PA in all periods of life, reaching the appropriate PA level (PAL) is particularly important in childhood and adolescence, since regular PA is essential for healthy growth and development during this life period for a number of reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a detailed clinical and neuropsychological evaluation was conducted by dementia experts, allowing for a classification of the participants’ cognitive status and enabling us to exclude participants with dementia from the analyses. What is more, all the questionnaires used for the assessment of the lifestyle factors have been previously used in the older population 38–40 . Another important strength is that both a priori and approaches were used for the extraction of the patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence of the relationship between physical activity and sleep remains inconsistent. While some studies demonstrated that objective sleep quality of nursing home residents with dementia was significantly improved by being physically active [ 36 , 37 , 38 , 39 ], other studies did not find a relationship [ 13 , 40 ]. Possible explanations for these mixed results are the differences in the individuals and environments, as well as a lack of consistency of sleep and activity measures across studies.…”
Section: Discussionmentioning
confidence: 99%